Evaluation of patient‐reported outcome measures of functional recovery following caesarean section: a systematic review using the consensus‐based standards for the selection of health measurement instruments (COSMIN) checklist. (20th August 2019) - Sharawi, N.; Klima, L.; Shah, R.; Blake, L.; Carvalho, B.; Sultan, P.
Summary: We performed a systematic review using 'consensus‐based standards for the selection of health measurement instruments' (COSMIN) criteria to identify and evaluate the quality of patient‐reported outcome measures (PROM) instruments that have been utilised to assess functional recovery following caesarean section, and determine the optimal instrument for use in this setting. A literature search was performed using five databases. Studies were included if a psychometrically validated instrument was used to assess functional recovery following caesarean section. The COSMIN appraisal checklist was utilised to: assess the quality of included studies reporting PROMs; determine psychometric quality of instruments; and identify the most promising instruments for use after caesarean section. We identified 13 PROMs used to assess the quality of recovery after caesarean section in 20 studies that included 9214 patients. All PROMs contained between two and seven domains. Five out of the 13 PROMs were specific to postpartum recovery. Only two of these PROM instruments were specifically designed for use after caesarean section (Obstetric Quality of Recovery‐11 and Recovery from Caesarean Section Scale). We found very few adequate measures of functional recovery following caesarean section. Overall, the Obstetric Quality of Recovery‐11 achieved the highest COSMIN standards for any PROM. Future development of PROMs for use after caesarean section should include multiple domains, and undergo validation as outlined by the COSMIN criteria.